Socrates - Rascal (San Francisco : Chronicle Books, 1993)
When Socrates, a homeless dog, finds a pair of eyeglasses in the street, the incident benefits him in more ways than one.
Keywords: Dogs - Fiction; Eyeglasses - Fiction